General overview of the growth and development of the services provided by Virtual Library of Serbia network and their impact on collection of statistical library data in Serbia - Cano Tomic, Emina; Ljubišić, Ljubica (Qualitative and Quantitative Methods in Libraries, 2020)
Virtual Library of Serbia is a project linking Serbian libraries into a single information system based on the COBISS platform, allowing shared cataloguing, access to foreign databases and automation of all library services. The network was launched in 2003 with establishment of a shared union catalogue integrating the bibliographic catalogues of the four largest libraries in the country (which was re-launch, actually, as the first attempt to develop such network took place from 1988 to 1992 in former Yugoslavia). In 2006, the web application E-CRIS.SR was developed in compliance with the CERIF recommendations. It is established as a register of researchers and organisations included in the national library information system and COBISS.Net  regional network. After fifteen years, the system has grown to include more than two hundred libraries (2 national, 94 public, 83 university/academic and 23 special libraries). In this paper we present and overview of the growth and development of the network and demonstrate all advantages of library networking for collection of data and processing of all kinds of library related statistical information in Serbia.